2018
DOI: 10.18632/oncotarget.25693
|View full text |Cite|
|
Sign up to set email alerts
|

Lung cancer susceptibility from GSTM1 deletion and air pollution with smoking status: a meta-prediction of worldwide populations

Abstract: Glutathione S transferase mu 1 (GSTM1) gene has been associated with lung cancer (LC) risk, for GSTM1 enzyme playing a vital role in detoxification pathway and protective against toxic insults. The major objective of this study was to investigate GSTM1 deletion pattern and its association with LC in the world’s population by using meta-prediction techniques. The secondary objective was to examine the effects of air pollution, smoking status, and other factors for gene-environment interactions with GSTM1 deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…GSTM1 has been studied as a lung cancer susceptibility gene due to its involvement in the detoxification of tobacco smoke. Germline variants have been associated with lung cancer risk in numerous populations (33). Molecular studies also report enhanced platinum sensitivity in lung cancer cell lines when targeting GSTM1 with analogue inhibitors suggesting a role in multidrug resistance pathways (34).…”
Section: Discussionmentioning
confidence: 99%
“…GSTM1 has been studied as a lung cancer susceptibility gene due to its involvement in the detoxification of tobacco smoke. Germline variants have been associated with lung cancer risk in numerous populations (33). Molecular studies also report enhanced platinum sensitivity in lung cancer cell lines when targeting GSTM1 with analogue inhibitors suggesting a role in multidrug resistance pathways (34).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with the theoretical perspectives on smoking, programmed cell death, and the GSTM1 gene’s role in lung carcinogenesis. The GSTM1 gene detoxifies metabolites of environmental carcinogens like tobacco smoke ( Kabesch et al, 2004 ; Reuter et al, 2010 ; Zhu et al, 2013 ; Yang et al, 2015 ; Adibhesami et al, 2018 ; Yu et al, 2018 ; Arfin, 2021 ; Zhang et al, 2022 ). Its deletion or inadequacy increases susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Glutathione S Transferase mu 1 (GSTM1) gene has been linked with lung cancer risk, as it plays a role in toxicity and detoxification ( Zhang et al, 2022 ). Deleting this gene has increased the risk of lung cancer ( Yu et al, 2018 ). Thus, smoking and GSTM1 play significant health roles.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of epidemiological studies have associated the GSTM1 null genotype with enhanced risk of prostate cancer (28, 29) and cancer at other sites (30–32), and several epidemiological studies have reported that the beneficial effect of diets rich in cruciferous vegetables in reducing cancer risk is modified by GSTM1 genotype (33–37). Experimental human dietary intake studies with biological markers have reported greater effect of isothiocyanate intake with GSTM1 null individuals than those with 1 or 2 GSTM1 alleles (38, 39).…”
Section: Discussionmentioning
confidence: 99%